E-book design preferences: A case study - Lim, Yan Peng; Ling, Siew Woei; Chong, Pei Fen (2008)
The purpose of this study is to investigate the students' preferences on page and content design of e-books. Three e-books in portable document format, which differ in contents, appearance and layout, are selected as study materials. An online survey is conducted, and 99 questionnaires are returned. Results of the study show that navigation design greatly affects overall ease of use of e-books; and appearance and content design have a great impact on the users' overall impression on the e-books. The findings of this study are especially beneficial for e-book designers and academicians who are interested to venture into e-books.